Territorial Bestowals to Subordinate Nayaks in Tamilnadu under Krishnadevaraya – An Epigraphical Study - Mrs. M. Aashath Parvin; Dr. J. Murugan Ph.D (Revista Electronica de Veterinaria, 2024)
Tamilnadu under Vijayanagar rule witnessed a new politico-military framework centred on military establishments. The representative rule in the rajyams evolved later into the Nayak and Poligar Systems. Meanwhile the subinfeudation or the subordinate nayak system was strengthened under Krishnadevaraya in the regions under Vijayanagar empire. Such system is identified in the Vijayanagar epigraphs of Tamilnadu during the medieval period. Those subordinate nayaks were bestowed with nayakkattanam and assigned with sirmai, and its related delegations by the Vijayanagar rulers. The graded delegation of power, hierarchical transfer of fiscal and military responsibility and the services of subordinate nayaks in Tamilnadu under Krishnadevaraya is studied in this article by analyzing their epigraphs.